Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar Siswa Sekolah Dasar Negeri 111/IX Muhajirin - Wara Supatni (Universitas Batanghari Jambi, 2020)
The problem examined in this study is the lack of maximum utilization of school libraries as learning resources. Focus of the problem: how to use the school library as a learning resource for students of SDN 111 / IX Muhajirin Village. The purpose of this study is to describe the use of school libraries as learning resources for students of SDN 111 / IX Muhajirin Village. The approach used in this research is qualitative. This type of research is descriptive research. This research was conducted from class I-VI SDN 111 / IX Muhajirin Village in February-April 2019. The subjects in this study were students of class I-VI SDN 111 / IX Desa Muhajirin, totaling 30 people consisting of 16 males and 14 women, homeroom teacher, librarian, and principal. Collecting data in this study using observation sheets, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results showed that the use of the school library as a learning resource was not optimal. So, it can be concluded that the use of school libraries as a learning resource for students of SDN 111 / IX Muhajirin Village has not run optimally.